1996
DOI: 10.1007/bf02257524
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal-induced alteration to root architecture in strawberry and induced resistance to the root pathogenPhytophthora fragariae

Abstract: Three strawberry cultivars Elsanta, Cambridge Favourite and Rhapsody were inoculated with either Glomus fasciculatum or GIomus etunicatum and their growth compared with non-inoculated plants. The roots of all inoculated plants were 55 to 70% colonised after 98 days. Increases in both root and shoot dry weights were measured. Root architecture was atso determined and increases in branching were evident in AMF colonised root systems. The remaining plants were then inoculated with the root pathogen Phytophthorafr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
3
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 16 publications
3
66
3
2
Order By: Relevance
“…Norman et al [65] observed that strawberry plants cv. "Elsanta", "Cambridge favourite" and "Rhapsody" inoculated with AMF increased root weight, and root colonisation, three months after inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Norman et al [65] observed that strawberry plants cv. "Elsanta", "Cambridge favourite" and "Rhapsody" inoculated with AMF increased root weight, and root colonisation, three months after inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…The species G. fasciculatum and G. etunicatum induced modification in the roots of the Elsanta and Cambridge Favorite strawberry cultivars, but did not cause any alteration in the morphology of the roots of the Rhapsody cultivar, shedding the variable effect of these AMF species on different cultivars of the same plant species (Norman et al, 1996).…”
Section: Anatomy and Morphology Changes In Rootsmentioning
confidence: 86%
“…However, the relationships involved in the formation of this symbiosis, since the signaling between the phytobionts, the early stages of the colonization process, as well as possible alterations in the morphological structure of the roots (Berta et al, 1995), in order to be considered a complete understanding relations between the symbionts There is little information about such relationships, as well as morphological changes produced by mycorrhizal infection in plant tissues . Some authors report that the AMF does not cause major morphological changes in roots (Cooper, 1984), but studies showed that the AMF induces changes in the architecture (Berta et al, 1995;Norman et al, 1996), especially in the increase of the root ramification, in the morphology (Berta et al, 1995;Bressan & Vasconcelos, 2002;Kothari et al, 1990;Norman et al, 1996,) and the anatomy (Berta et al, 1995) the roots of different plant species.…”
Section: Introductionmentioning
confidence: 99%
“…(Norman et al, 1996). Caravaca et al (2003) showed that the root mass of Dorycnium pentaphyllum plants inoculated with Glomus intraradices increased by 116% compared to that observed in non-mycorrhizal plants.…”
Section: Fig4 : Mycorrhization Parameters Of the Argan Roots After Tmentioning
confidence: 99%